PENGARUH EFISIENSI MODAL KERJA TERHADAP PROFITABILITAS KOPERASI SERBA USAHA - Kumara, Dewa Putu; Dharma Suputra, I Dewa Gde (E-Jurnal Akuntansi, 2014)
12.00 Cooperative is a legal entity that does business with aim of improving the welfare of members and surrounding communities. This research aims to determine the effect of current assets turnover, fixed assets turnover, total assets turnover, and working capital assets turnover on profitability Koperasi Serba Usaha in Kecamatan Penebel in 2010 to 2012. The analysis method used is multiple linear regression. The results of hypothesis-tests found that partially the current assets turnover has a negative significant effect on profitability, total assets turnover has a positive significant effect on profitability and working capital turnover has a negative significant effect on. 12.00 Normal 0 false false false EN-US X-NONE X-NONE Normal 0 false false false EN-US X-NONE X-NONE
Keywords: profitability, CAT, FAT, TAT, WCT